An Automatic Wind Turbine Braking System on PLTH Bayu Baru through a Fuzzy Logic Controller - Tole Sutikno; Syahid Hikmatul Wahid; Rizky Ajie Aprilianto; Arsyad Cahya Subrata; Auzani Jidin (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
PLTH Bayu Baru is one of the hybrid power plants (HPP) located in Baru beach, Pandansimo, Bantul, Yogyakarta, Indonesia. It generates electrical energy from two sources, wind and solar energy. However, a problem is encountered regarding wind turbine mechanics due to using a manual switch for braking during periods of excessive wind speed. This study proposes an automatic wind turbine braking system through a utilized fuzzy logic controller (FLC) for the PLTH Bayu Baru application. The Mamdani type FLC without complex mathematical models is applied to the Arduino Uno development board to realize the proposed systems. The error (Error_V) and delta error (dError_V) values from the generator voltage sensor become the input of the proposed systems, while the pulse width modulation (PWM) becomes the output for controlling the on/off period of the MOSFET as switching devices. The proposed systems have been tested on a micro-scale wind turbine with PMSG 12V/400W type. From the testing results, the proposed system successfully braked automatically at the point wherein the generator voltage exceeds the setpoint value. Also, the proposed system keeps the generator voltage less than 13.8V, so the problem caused by excessive speed can be resolved.